PENGARUH BRAND AMBASSADOR, BRAND PERSONALITY DAN KOREAN WAVE TERHADAP KEPUTUSAN PEMBELIAN - Tri Widarmanti; Widya Amalia Cahyani (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to determine whether there is influence of brand ambassadors, brand personality and the Korean wave on purchasing decisions of Nature Republic and how influential these three variables are on purchasing decisions of Nature Republic products. This research was conducted using a quantitative method by distributing questionnaires online. The population of this study are people who have used Nature Republic products. The sample in this study was 100 respondents and the data was processed using SPSS 25 software with multiple linear regression analysis techniques. The results of this study show that brand ambassadors, brand personality and the Korean wave simultaneously influence purchasing decision variables significantly. Partially, brand ambassadors do not positively and significantly influence the purchasing decisions of Nature Republic products, brand personality influences the purchasing decisions of Nature Republic products positively and significantly, the Korean wave influences the purchasing decisions of Nature Republic products positively and significantly.